Cultural mapping of teachers’ spatial agency and social practices - Aryasatya Rafa Prayitno (Journal of Environment and Geography Education, 2025)
Background: Fluctuating policy changes, the demand for rapid adaptation, and high socio-cultural expectations for producing ideal students generate systemic pressure among Indonesian teachers. Such pressure requires analysis beyond administrative or psychological metrics toward the spatial contexts in which teaching is actually lived. Methods: This study analyzes how teachers’ social practices shape and are shaped by the spatial dynamics of their daily lives and workplaces, positioning them as active agents in the production of educational space. A qualitative, intensive contrastive case study was conducted with three active teachers (N = 3) across diverse spatial contexts. Complementary spatial analysis using ArcGIS slope mapping was applied to contextualize topographical risk, enriching interpretation of teachers’ lived geographies. Data were gathered through participatory mapping workshops that produced story maps, complemented by map-based interviews, and analyzed through cross-case thematic analysis. Findings: Findings indicate that professional stress materializes into risk-prone geographies, countered by three primary spatial tactics: symbolic deviation, social-informational capital, and hedonic compensation or role integration. Topographical slope analysis further corroborates teachers’ narratives of risk-prone mobility, revealing how physical gradients materially condition professional stress and spatial inequity. Conclusion: These results suggest that teacher resilience is an active, spatially produced phenomenon contingent upon the symbolic transformation of ordinary materiality. Recognizing the material and emotional dimensions of educational space provides a foundation for designing spatially responsive well-being programs and geographically equitable teacher policies. Novelty/Originality of this article: This study introduces a spatial lens on teacher resilience within Indonesia’s educational geography, advancing the methodological integration of cultural mapping and topographical analysis in understanding lived pedagogical space.